EVALUASI PENGGUNAAN OBAT ANTIHISTAMIN PADA PASIEN PENYAKIT KULIT DI APOTEK GEJAYAN DEPOK SLEMAN - Qarriy Aina Urfiyya; Danang Yulianto; Rita Nur Fitriana (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2023)
Abstract Background: Skin disease was included in the top ten diseases at the Yogyakarta regional health center in 2014. Skin disease can be caused by infection or allergies. One of the drugs used to treat skin diseases is antihistamines. Objective: To evaluate the use of antihistamines in patients with skin diseases at the Gejayan Pharmacy, Depok, Sleman for the November-December 2021 period. Method: This study used an analytic observational method, with retrospective data collection. Sampling used a purposive technique on prescriptions and medical records of skin disease patients for the November-December 2021 period, a total of 286 samples. Data were analyzed descriptively quantitatively on patient characteristics, use of antihistamines, and evaluation of the use of antihistamines in terms of the right drug and the right dose. Results: The results of this study showed that there were 84.3% of skin disease patients aged 15-64 years, and 15.7% aged ≥ 65 years. Patients with female sex of 57.7% and male by 42.3%. The highest patient diagnoses were contact dermatitis at 24.5%, atopic dermatitis at 12.9% and urticaria at 10.1%. The most widely used type of antihistamine drug was CTM with 22.7%, followed by ryzicor with 17.1% and river with 9.1%. Conclusion: Evaluation of drug use based on the right drug is 96.8% and the right dose is 100%.